HUBUNGAN CATCH PER UNIT EFFORT IKAN PELAGIS KECIL DENGAN PARAMETER LINGKUNGAN DI JMF TRIANGLE - Panggabean, Donwill (Politeknik Kelautan dan Perikanan Karawang, BRSDM KP., 2024)
The production of capture fisheries in a water area can increase or decrease, this is known from the value of Catch per Unit Effort (CPUE). This study aims to calculate the CPUE value of small pelagic fish in the JMF triangle and explain correlation of CPUE with environmental factors (sea surface temperature and chlorophyll-a). The data analyzed were Aqua-MODIS image, SNPP-VIIRS image, and capture data. The analysis used simple correlation and regression tests to determine the relationship of CPUE to sea surface temperature (SST) and chlorophyll-a, further strengthened by overlay techniques for its descriptive. Information is presented in the form of spatial and temporal thematic maps and infographics. The results showed a trend of increasing the total CPUE of small pelagic fish production for the 2012-2015 period. The highest seasonal CPUE occurs in the Western Season period, and the lowest in the Transitional Season II. The highest CPUE value occurred in January 2013 with a value of 0.54 tons/ship, while the lowest CPUE was in September 2015 with a value of 0.052 tons/ship. Layang, Banyar and Bentong species responded negatively to SST, especially in the Eastern Season, while Lemuru showed no direct relationship to SST. Lemuru's response to chlorophyll-a showed a positive value, where it was seen that an increase in chlorophyll-a concentration was followed by an increase in CPUE, while Layang, Banyar and Bentong showed that an increase in the value of chlorophyll-a concentration did not directly affect the increase in the CPUE value of the three species.